Contrast-Enhanced Ultrasound as a New Investigative Tool in Diagnostic Imaging of Muscle Injuries—A Pilot Study Evaluating Conventional Ultrasound, CEUS, and Findings in MRI. Issue 4 (July 2018) - Hotfiel, Thilo; Heiss, Rafael; Swoboda, Bernd; Kellermann, Marion; Gelse, Kolja; Grim, Casper; Strobel, Deike; Wildner, Dane
Abstract : Objective: To emphasize the diagnostic value of contrast-enhanced ultrasound (CEUS) in the imaging of muscle injuries with different degrees of severity by comparing findings to established imaging modalities such as conventional ultrasound and magnetic resonance imaging (MRI). Design: Case series. Setting: Institutional study. Conventional ultrasound and CEUS were performed in the Department of Internal Medicine. Magnetic resonance imaging was carried out in the Department of Radiology within the Magnetom Avanto 1.5T and Magnetom Skyra fit 3T (Siemens Healthineers, Erlangen, Germany) and in the Institution of Imaging Diagnostics and Therapy (Magnetom Avanto 1.5T; Siemens, Erlangen, Germany). Patients: Fifteen patients who underwent an acute muscle injury were recruited. Main Outcome Measures: The appearance and detectable size of muscle injuries were compared between each imaging modality. The injuries were assessed by 3 independent observers and blinded between imaging modalities. Results: All 15 injuries were identified on MRI and CEUS, whereas 10 injuries showed abnormalities in conventional ultrasound. The determination and measurement revealed significant differences between conventional ultrasound and CEUS depending on injury severity. Contrast-enhanced ultrasound revealed an impairment of microcirculation in grade I lesions (corresponding to intramuscular edema observed in MRI), which was not detectable using conventional ultrasound. Conclusions: Our results indicate that performing CEUS seems to be a sensitive additional diagnostic modality in the early assessment of muscle injuries. Our results highlight the advantages of CEUS in the imaging of low-grade lesions when compared with conventional ultrasound, as this was the more accurate modality for identifying intramuscular edema.